Looking for traces of Hawking radiation in correlation functions of BEC acoustic black holes - Anderson, Paul Raymond; Balbinot, Roberto; Dudley, Richard Allen; Fabbri, Alessandro (Comptes Rendus. Physique, 2025)
Renaud Parentani was one of the leading figures in Quantum Field Theory in curved spacetime, in particular concerning its applications to Hawking-like radiation in analogue models. In this paper dedicated to him, we discuss the characteristic features appearing in the correlation functions in an acoustic black hole formed by a Bose–Einstein condensate, considered as signature of the presence of Hawking radiation in this system.